2013
DOI: 10.1590/s1809-98232013000300008
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da estimulação diafragmática elétrica transcutânea na função pulmonar em idosos

Abstract: ResumoIntrodução: O envelhecimento promove mudanças em diversos sistemas orgânicos, inclusive no respiratório, evidenciando alterações nos centros reguladores da ventilação, nos quimiorreceptores, na densidade óssea da caixa torácica, além de diminuição da força dos músculos inspiratórios. Objetivo: Avaliar o efeito de um programa de treinamento específico da musculatura respiratória por meio da estimulação diafragmática elétrica transcutânea (EDET) sobre a função pulmonar de idosos. Método: 21 idosos foram di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
16

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 20 publications
0
3
0
16
Order By: Relevance
“…The reduction in FEV 1 in the elderly may signify obstructive changes, which can be explained by a decrease in elastic lung retractility, a reduction in chest wall compliance and a reduction in the strength of the respiratory muscles, leading to the progressive decline in lung function over time. 19,20 With respect to the decrease in respiratory muscle strength, Santos et al 21 suggested the application of respiratory muscle training among this population, as this can potentiate the respiratory muscles of the elderly and thus constitute a preventive strategy against the decline of respiratory muscle strength and pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in FEV 1 in the elderly may signify obstructive changes, which can be explained by a decrease in elastic lung retractility, a reduction in chest wall compliance and a reduction in the strength of the respiratory muscles, leading to the progressive decline in lung function over time. 19,20 With respect to the decrease in respiratory muscle strength, Santos et al 21 suggested the application of respiratory muscle training among this population, as this can potentiate the respiratory muscles of the elderly and thus constitute a preventive strategy against the decline of respiratory muscle strength and pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…Another 21 Debastiani and Aroca verified that the TEDS application in institutionalized older people, after 10 sessions of 20 minutes, provided an increase of up to 25% on MIP. 22 Unlike previous findings, the present study identified a decrease in MIP and MEP values, although these data were not statistically significant.…”
Section: Discussionmentioning
confidence: 87%
“…Os resultados obtidos após a intervenção acerca de V', VC e FR, quando comparado entre os grupos, corroboram com os achados na literatura, a exemplo dos estudos de Santos et al 11 , os quais utilizaram a EDET para melhorar a função respiratória em 21 idosos saudáveis, do sexo masculino, com faixa etária compreendida entre 67 e 79 anos, não fumantes, e sem história de doença pulmonar, neuromuscular ou alterações posturais. Ao final do estudo a EDET promoveu incremento no VC.…”
Section: Discussionunclassified